Actinide Recovery From Waste Processing Salts - B. Mishra (The Minerals, Metals and Materials Society, 1994)
Several reactive metal purification processes using molten salts generate effluent from which significant quantities of metal can be recovered prior to discardinglrecycling the salt. A Salt-scrub [SS] process has been applied where the reactive metals are recovered as a metal-gallium alloy by calciothermic reduction of the metal compounds. The SS alloy compositions were produced by mixing, pressing and sintering the metal-powders. Measurement of metal recovery has been studied for cerium, silver, tin and lead. The process has been optimized for variables such as the metal quantity per kg of effluent salt, amount of excess calcium over stoichiometry, stirring rate and time and holding time at reduction temperature. Over ninety-seven percent metal recovery has been obtained under optimized conditions. The development of an alloy for efficient Salt Scrub processing reduces a major contaminated waste disposal problem as well as recovering the valuable reactive metal. Surrogate metals have been used in this work to study the behavior of plutonium.